1992
DOI: 10.3133/ofr92527
|View full text |Cite
|
Sign up to set email alerts
|

Properties and hazards of 108 selected substances

Abstract: Ranking of the 108 selected substances by electrical resistivity.Ranking of the 108 selected substances by ionization potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 80 publications
0
13
0
1
Order By: Relevance
“…The literature search during the compilation by Lucius, et al (1989) revealed little published information about contact angles. The purpose of this paper is to make available the measured contact angles of water, mercury, and 20 organic liquids on substrates of quartz, calcite, biotite, and Ca-montmorillonite.…”
Section: Introductionmentioning
confidence: 99%
“…The literature search during the compilation by Lucius, et al (1989) revealed little published information about contact angles. The purpose of this paper is to make available the measured contact angles of water, mercury, and 20 organic liquids on substrates of quartz, calcite, biotite, and Ca-montmorillonite.…”
Section: Introductionmentioning
confidence: 99%
“…2). LNAPL is characterized by a very high resistivity and a dielectric constant around 2, according to several authors (Lucius et al 1989;Rocha and Simoes-Moreira 2005;Zaitsev et al 2017) (Table 2). The LNAPL causes 5 cm of water table rise, from 25 to 20 cm (Fig.…”
Section: Cell Set-up and Data Acquisitionmentioning
confidence: 99%
“…Toluene represents the BETX family of groundwater contaminants (benzene, ethylbenzene, toluene, and xylenes) found in association with leaking underground gasoline and diesel fuel storage tanks [ Swoboda‐Colberg , 1995]. BEHP, one of the 10 most commonly occurring groundwater contaminants, is listed as a priority one hazardous substance [ Lucius et al , 1992], and has been deemed undetectable by noninvasive geophysical methods [ Olhoeft , 1992]. We focus on the effects of clay content and concentration of iron on mineral surfaces on our ability to accurately quantify these two contaminants.…”
Section: Introductionmentioning
confidence: 99%